36th AIAA Aerospace Sciences Meeting and Exhibit 1998
DOI: 10.2514/6.1998-593
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of wake vortices interacting with the ground

Abstract: Although wake vortices are known to decay more rapidly near the ground than away from the ground, the details of the ground interaction are not well understood. Propeller anemometer arrays located under the approach path have been used to study vortex transport and provide some information about the vortex interaction with the ground, such as the generation of secondary vortices via boundary-layer detachment. A propeller anemometer array at John F. Kennedy International Airport using 8.5-m poles was augmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 1 publication
1
20
0
1
Order By: Relevance
“…Although not shown here, the A-300, A-310, A-319, and A-320 showed the same results. (A review of previous data collection efforts 3,7,19 showed a similar result.) NonDimensional Units Vortex Survival Probability…”
Section: Effect Of Turbulencesupporting
confidence: 52%
See 2 more Smart Citations
“…Although not shown here, the A-300, A-310, A-319, and A-320 showed the same results. (A review of previous data collection efforts 3,7,19 showed a similar result.) NonDimensional Units Vortex Survival Probability…”
Section: Effect Of Turbulencesupporting
confidence: 52%
“…This works well for vortices at altitude and has been used with some success for vortices near the ground. 7,19 However, because of the presence of the ground, the inertial subrange concept might be inadequate.…”
Section: Effect Of Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the previous work has been based on vortex flow in the free-stream and the interaction of vortices and boundary layers has been less discussed. The development of vortices in the wake of an aircraft at take-off and landing involves the interactions with the ground surface and has important safety applications [8]. The vortices are forced into the ground surface owing to the downwash effect, subsequently inducing boundary layer separation and the generation of secondary vortices with opposite vorticity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Behavior of wake vortices is widely shown to be altered by proximity to the ground [5][6][7], as well as by various atmospheric conditions [8,9]. A numerical simulation by Corjon and Poinsot [5] finds that ground proximity and resulting viscous flow produce a secondary pair of vortices that induce the original wake vortices to move upward; experimental studies confirm formation of secondary vortices as a result of proximity to the ground [6].…”
mentioning
confidence: 99%